2016
DOI: 10.1002/apj.2019
|View full text |Cite
|
Sign up to set email alerts
|

Study of gas–liquid mixing in stirred vessel using electrical resistance tomography

Abstract: Hamad (2016) Study of gas-liquid mixing in stirred vessel using electrical resistance tomography. Asia-Pacific Journal of Chemical Engineering . ISSN 1932ISSN -2143 Access from the University of Nottingham repository: http://eprints.nottingham.ac.uk/35359/1/Manuscript%20ERT.pdf Copyright and reuse:The Nottingham ePrints service makes this work by researchers of the University of Nottingham available open access under the following conditions. This article is made available under the University of Nottingham E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…The development of polymer nanocomposites has produced a new class of materials with superior mechanical, thermal, and transport properties . These properties depend on several factors, such as the polymer synthesis method, the mixing process, and the nanoreinforcement . In this regard, Cordero et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of polymer nanocomposites has produced a new class of materials with superior mechanical, thermal, and transport properties . These properties depend on several factors, such as the polymer synthesis method, the mixing process, and the nanoreinforcement . In this regard, Cordero et al .…”
Section: Introductionmentioning
confidence: 99%
“…11,12 The development of polymer nanocomposites has produced a new class of materials with superior mechanical, 13 thermal, 14 and transport properties. 15 These properties depend on several factors, such as the polymer synthesis method, 16,17 the mixing process, 18 and the nanoreinforcement. 13 In this regard, Cordero et al 19 found that the incorporation of a small amount of nanocellulose obtained by hydrolysis can have a substantial improvement of the mechanical properties of polyurethane foams (PUFs) synthesized from castor oil.…”
Section: Introductionmentioning
confidence: 99%
“…Some related studies about gas-liquid mixing and visual analysis techniques have already been carried out. Farooq Sher et al [30] developed an innovative approach to address the Appl. Sci.…”
Section: Type Of Pump Advantage Disadvantagementioning
confidence: 99%
“…[25,26] Nevertheless, due to the strong intermolecular forces, Gr is extremely keen to aggregate, becoming the predominant obstacle to the large-scale application of Gr. [27,28] Aside from previous recognitions that external forces including ultrasound, ball mill or mechanical mixing are key aspects in inducing exfoliation and uniform dispersion of Gr layers the surface chemistries of exfoliated nanolayers are recently found to play a vital role in achieving desired properties of the Gr-based composite. [29,30] Grafting an ionic liquid (IL) onto the surface of graphitic carbons can facilitate exfoliation and uniform dispersion of Gr to improve the performance of carbon composite materials due to the mutual exclusion between the π electrons of the carbons and the positive charge of IL.…”
Section: Introductionmentioning
confidence: 99%